Keynes and the drunkard under the lamp post: Making sense of Palley - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2023)
In a recent article, Tom Palley begins his critique of Keynesian economics with the well-known story of a drunkard who, when searching for his lost keys, looks not in the darkness of the nearby lawn where he misplaced them, but instead under the light cone of a lamp post because, when asked, he replies that's where the light is. This story serves as a metaphor for the field of economics attempting to understand the workings of the capitalist economy solely through the lens of Keynesian economics. However, this endeavour is ultimately futile as comprehending capitalism requires a different analytical approach: acknowledging social conflict as an essential component of capitalism's nature better addressed by Kaleckian macroeconomics. I attempt to illustrate that Palley is accurate in emphasizing the paradigmatic differences and even incommensurabilities between Keynes' monetary production paradigm and the Marxian-Kaleckian social conflict paradigm. This suggests that any classification under the umbrella term "post-Keynesianism" is misleading. However, Palley is mistaken in his assertion that this distinction aligns Keynes' economics with neoclassical (mainstream) economics, as the acceptance or rejection of social conflict is not the only fault line in terms of ontology. There are other ontological divisions that can exist. Or, to use the metaphor, the lamp post can be moved to different areas of the lawn, indicating different ontological perspectives.
Keywords: A14; B40; B51; E11; E12; 330; Keynes; social conflict; effective demand; monetary production